THE EFFECT OF BINJAI (Mangifera caesia) LEAVES EXTRACT GEL TO COLLAGEN FIBER DENSITY ON WOUND - Novia Damayanti; Irham Taufiqurrahman; Juliyatin Putri Utami (FKG Unlam, 2022)
Background: Binjai (Mangifera caesia) leaves extract contains flavonoid, saponin, phenolic, tannin, alkaloid and triterpenoid. The said contents are known to help the process of wound healing. Gel formations contains a lot of water, resulting in substance penetration into the tissue will be better if used as wound healing adjuvant therapy. Purpose: To analyze the effect of binjai leaves extract gel (Mangifera caesia) that topically given to collagen fiber density on the wistar rat incision wound. Methods: This research was a true experimental with post test only with control group design that consists of 4 groups. Group I has been given the placebo gel as control, group II, III and IV have been given the binjai leaves extract gel with 5%, 10% and 15% concentration that observed on the 7th day and 14th day. The collagen fiber density assessed by measuring hydroxyproline with Stegmann and Stalder method. Results: The research result shows that the 15% concentration of binjai leaves extract gel has a better effect on collagen fiber density compared to 5% and 10% concentrations. Two-way Anova data analysis revealed that the significant difference average of collagen fiber density of the whole group with the value of sig.p < 0,05. Conclusion: The 15% concentration of binjai leaves extract gel has the most optimal effect compared with the 5% and 10% concentrations to collagen fiber density on the wistar rat incision wound.